JUVENILE JUSTICE SYSTEM AND ADOLESCENT MENTAL HEALTH - Verma, Vijay Kumar; Singh, Prof.(Dr.) Sushil Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Juvenile offenders in India face significant mental health challenges that impede their rehabilitation and reintegration into society. This paper examines the prevalence and nature of these challenges, systemic gaps in addressing them, and socio-cultural factors contributing to their marginalization. This study, using existing literature and legal frameworks, highlights the urgent need for mental health services within the juvenile justice system to promote effective rehabilitation of minor offenders and reduce recidivism of juvenile crimes. Furthermore, this research researchers aim to analyze the steps taken by the Indian government to improve the mental health of adolescents in conflict with the law and the challenges faced in their implementation.